Reflex impairment and physiological stress response in the Neotropical wolf fish Hoplias malabaricus (Characiformes, Erythrinidae) exposed to catch-and-release angling - Andrade, Laura Simões; Garrone-Neto, Domingos [UNESP]; Sales, Manuela Alves Nobre [UNESP]; Souza-Bastos, Luciana Rodrigues de; Souza, Ursulla Pereira; Sadauskas-Henrique, Helen (Elsevier, 2021)
Catch-and-release (C&R) angling is rapidly increasing in many tropical countries. In South America, the common wolf fish Hoplias malabaricus (also named as “trahira”) has a widespread distribution and is highly targeted by C&R anglers. However, no data about C&R effects on the species are available. Thus, hook injuries, reflex impairment, and physiological parameters relative to C&R angling were quantified in individuals of H. malabaricus submitted to minimum fight time (control; treatment 1) and air exposed for 30 and 60 s (treatments 2 and 3, respectively). Most fish (n = 46) were hooked in non-critical locations, while 14 had wounds at critical locations. Forty-three of the 60 fish caught exhibited reflex impairment, but without statistical differences among the control and the air exposed groups. Fish weight had significant contribution to reflex impairment, which individuals with smaller weight had a higher impairment of reflexes than heavier individuals. No differences in physiological parameters (glucose, lactate, K+, osmolality) were found between the treatments. Plasma concentrations of Na+ increased in relation to air exposure, while differences in plasma concentration of K+ were related to fish weight. These findings suggest that H. malabaricus is resilient to C&R angling when fight and handling times are short, but that smallest individuals are more susceptible to reflex impairment, especially in warmer waters. The low levels of basal glucose presented by H. malabaricus revealed to be an important information when evaluating the effects of the C&R on fish species tolerant to hypoxia, once could lead to bias in data interpretation and, consequently, in C&R evaluation. Thus, anglers and fisheries managers need to be aware this information, in order to support sustainable C&R angling of H. malabaricus (and also for its congeners) while increasing environmental awareness and stimulating recreational fishing tourism in South America.
Keywords: Catch-and-release; Fishing tourism; Recreational fishing; Reflex action mortality predictors; Stress response